Implementation of Problem Based Learning (PBL) Model to Improve Indonesian Language Learning Outcomes in Grade IV Students of MI Sudirman Banyuanyar. - Abadi, Zaenal (Jurnal Cendekia Islam Indonesia, 2025)
This study aims to improve the learning outcomes of Indonesian language of grade IV students of MI Sudirman Banyuanyar through the Problem Based Learning (PBL) learning model. This study uses a classroom action research (CAR) method consisting of four stages, namely: Planning, Implementation, Observation, and Reflection. The subjects of this study were grade IV students of MI Sudirman Banyuanyar. Data collection techniques were in the form of observation and tests. The results of the first cycle of the study showed 68,56% and the second cycle showed 86,18%. The success of this study cannot be separated from the efforts of teachers in using learning models that are appropriate to the needs of students, namely Problem Based Learning (PBL). Thus, it can be said that the Problem Based Learning (PBL) learning model can improve the learning outcomes of Indonesian language in grade IV students of MI Sudirman Banyuanyar.